Induced abortion in Iran, Tehran University of Medical Sciences, the law and the diverging attitude of medical and health science students. - Mohammad Haddadi; Leyla Sahebi; Fatemeh Hedayati; Iqbal H Shah; Mohammadamin Parsaei; Mamak Shariat; Mohadese Dashtkoohi; Sedigheh Hantoushzadeh (PLoS ONE)
Background The topic of induced abortion has been a subject of extensive debate among various moral and religious frameworks and continues to pose significant challenges within the domains of medical ethics and policy formulation. In the context of Iran, an Islamic republic, the approach to induced abortion has been notably influenced by historical, social, and political dynamics. Following the implementation of the 'Rejuvenation of the Population and Protection of the Family Law (RPPF)' in 2021, access to induced abortion and contraceptive measures has been markedly restricted as a response to concerns surrounding population decline. Objective This study aims to assess the attitudes of Iranian medical and health science students toward induced abortion as future executives of health programs. Methods This cross-sectional study administered a structured questionnaire for self-completion to medical and health science students of Tehran University of Medical Sciences, including medical students, obstetrics and gynecology residents, and nursing and midwifery students. The scoring of responses was between ‒12 and + 12, with the score ranging from 0 to positive, 12 showing an attitude negative to induced abortion, and the score below zero to ‒12 reflecting a positive attitude toward induced abortion. Results A total of 237 participants were involved in the study, with 52% being female, and 60% originally from cities other than Tehran. The median (min, max) of the total score of the attitude toward induced abortion was ‒5.0 (12,10). The mean score varied by the age of the respondents, with ‒4.0 (‒12, 10) for those aged above 30 years compared to ‒5.0 (‒12,10) for those aged below 30 years (P-value = 0.043). The score was 0.0 (‒12,10) for married compared to ‒6.0 (‒12,10) among single participants (P-value < 0.001). The score for participants who agreed with RPPF was 0.0 (‒12,10), compared to a more positive attitude of ‒8.0 (‒12,9) for participants who disagreed (P-value < 0.001). Conclusion Iranian medical and health science students support induced abortion before 16 weeks of gestation. The attitudes of medical students who are future providers of health care and implementers of RPPF and other health laws are, therefore, at variance with current laws and policies.